ANALISIS KUALITAS LAYANAN WEBSITE TECHOMA.id TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN FRAMEWORK WEBQUAL 4.0 - Arsa Erjore Ginting (2024)
Developments in the use of websites are currently very fast, almost all companies already have websites with various purposes, ranging from displaying company profiles and information, marketing tools, improving service quality to researching buyer personas. The Techoma.id website was created with the aim of providing online Digital Marketing services for customers, both Business to Business (B2B) and Business to consumer (B2C) transactions. The products provided by the Techoma.id website are Social Media Management, Branding & Design, Video Production, Website Development. Webqual 4.0, which has 3 dimensions, namely usability, information quality, and service interaction quality, is a method for assessing the service quality of the Techoma.id website. The results of this research show that the average gap value in each dimension is negative. This shows that the quality of the current website does not meet user expectations. This is based on the expected value being greater than the actual value given to the service quality of the Techoma.id website. The results of the Importance Performance Analysis show that the statement variable attributes that are the main focus for improvement are in quadrant I, namely there are 6 statement variables with indicator codes US_2, US_7, IQ_1, IQ_3, IQ_6, and SQ_5.